A low-carbon cementitious material additive for concrete and preparation method thereof
By using a low-carbon gelling material additive composed of composite slag powder, composite gelling agent, etc. in concrete, the problem of high energy consumption and high carbon emissions in the cement industry is solved, and the mechanical properties of concrete are significantly enhanced. The amount of cement gel is used while reducing performance, and the CO2 emissions are reduced.
Patent Information
- Application Number
- CN202211614966.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-15
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-12-15
AI Technical Summary
The cement industry is an industry with high energy consumption and high carbon emissions. It is difficult for the existing technology to significantly reduce the amount of cement gel without reducing the performance of concrete, thereby reducing CO2 emissions.
A low-carbon gelling material additive for concrete is used, which consists of composite slag powder, composite gelling agent, water reducing agent, exciter, reinforcement, adhesive and stabilizer, and is made after stirring through a mixer. . The combined use of this additive can significantly enhance the mechanical properties of concrete and synergize with synergistic efficiency.
By using this additive, the mechanical properties of concrete can be significantly enhanced, while the amount of cement gel can be reduced without reducing the concrete properties, thereby reducing CO2 emissions.
Smart Images

Figure BDA0004000155700000071 
Figure BDA0004000155700000081 
Figure BDA0004000155700000082
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building material additives, and in particular relates to a low-carbon cementitious material additive for concrete and a preparation method thereof. Background Art
[0002] Concrete is a mixture of cement, sand and stone as aggregates, mixed with water (which may contain admixtures and additives) in a certain proportion, and mixed together to form a whole. Global climate change has significantly made greenhouse gas emissions, especially carbon emissions, a focus of widespread attention. The cement industry is an important basic raw material industry supporting social and economic development, and it is also an industry with high energy consumption and high carbon emissions. The comprehensive energy consumption of producing 1 ton of cement is about 113.5 kgce, and the emission is about 0.8 tons of CO2, accounting for 1 / 5 of the national industrial carbon emissions. The cement industry will face huge challenges and pressures in sustainable development and low-carbon economy.
[0003] The stages of CO2 emissions from cement production are divided into raw material processing, raw material preparation, fuel pretreatment, firing system, cement grinding, waste heat utilization and auxiliary production. Improving the utilization of alternative raw fuels, efficient coal combustion technology and equipment, optimizing new dry cement production lines, and efficient energy-saving grinding technology and equipment have made it very small to further reduce CO2 emissions. Minimizing the amount of cement gel without reducing the performance of concrete is a new idea to reduce CO2 emissions.
[0004] In the process of preparing concrete, cement generally accounts for about 50% of the total dry material mass. The amount used can be reduced to 30% through admixtures. If it is lower, the quality of concrete will be significantly reduced. The aggregate used in the process of preparing concrete is generally natural sand. The size of natural sand particles varies, and the size of natural sand particles from different sources often varies greatly, which significantly affects the mechanical properties of the prepared concrete and requires different additives to be mixed for optimization and modification. Summary of the invention
[0005] The purpose of the present invention is to provide a low-carbon cementitious material additive for concrete and a preparation method thereof.
[0006] A low-carbon cementitious material additive for concrete is prepared from the following raw materials in parts by weight: 80-120 parts of composite slag powder, 100-250 parts of composite gelling agent, 10-30 parts of water reducing agent, 6-18 parts of activator, 5-20 parts of reinforcing agent, 10-30 parts of adhesive and 10-30 parts of stabilizer.
[0007] The composite slag powder is a mixed slag obtained by mixing copper tailings powder and nickel tailings powder in a mass ratio of 3:1.
[0008] The composite gelling agent is a mixture of ferrous sulfate and polyvinyl acetate in a mass ratio of 3:1.
[0009] The water reducer is one or more of polyethylene glycol, calcium lignin sulfonate, aminobenzenesulfonic acid, polyethylene glycol methacrylate, and polycarboxylic acid water reducer.
[0010] The activator is one or more of water glass, aluminum sulfate and sodium metasilicate.
[0011] The reinforcing agent is one or more of vanadium slag, diatomaceous earth, white carbon black, calcium silicate whisker and basalt fiber.
[0012] The adhesive is one or more of epoxy resin, sodium carboxymethyl cellulose, gum arabic, polyacrylonitrile, styrene-butadiene rubber and polyacrylamide.
[0013] The stabilizer is one or more of oleic acid, triethanolamine, Wenlun gum, and montmorillonite.
[0014] The preparation method of the low-carbon cementitious material additive for concrete comprises the following steps: taking 80-120 parts of composite slag powder, 100-250 parts of composite gelling agent, 10-30 parts of water reducing agent, 6-18 parts of activator, 5-20 parts of reinforcing agent, 10-30 parts of adhesive and 10-30 parts of stabilizer in a mixer, and stirring the mixture at 600-1200 rpm for 30-60 minutes to prepare the low-carbon cementitious material additive for concrete.
[0015] The low-carbon cementitious material additive for concrete is used in preparing concrete with low cement dosage, wherein the dosage of cement in the concrete with low cement dosage is 15-30% of the mass of solid materials.
[0016] The beneficial effects of the present invention are as follows: the combined use of copper tailings powder and nickel tailings powder in the additive of the present invention can significantly enhance the mechanical properties of concrete prepared with natural sand as aggregate, and synergistically enhance the effect; using ferrous sulfate and polyvinyl acetate as composite gelling agents improves the slump of concrete slurry, and synergistically enhances the effect. DETAILED DESCRIPTION
[0017] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0018] Example 1
[0019] A low-carbon cementitious material additive for concrete is prepared from the following raw materials in parts by weight: 100 parts of composite slag powder, 180 parts of composite gelling agent, 20 parts of calcium lignin sulfonate, 12 parts of water glass, 12 parts of diatomaceous earth, 20 parts of styrene-butadiene rubber, 10 parts of oleic acid, and 10 parts of triethanolamine; the composite slag powder is a mixed slag obtained by mixing copper tailings powder and nickel tailings powder in a mass ratio of 3:1; the composite gelling agent is a mixture obtained by mixing ferrous sulfate and polyvinyl acetate in a mass ratio of 3:1.
[0020] The preparation method of the low-carbon cementitious material additive for concrete comprises the following steps: taking 100 parts of composite slag powder, 180 parts of composite gelling agent, 20 parts of calcium lignin sulfonate, 12 parts of water glass, 12 parts of diatomaceous earth, 20 parts of styrene-butadiene rubber, 10 parts of oleic acid and 10 parts of triethanolamine according to weight parts, putting them into a mixer and stirring them at 800 rpm for 40 minutes to prepare the low-carbon cementitious material additive for concrete.
[0021] Example 2
[0022] A low-carbon cementitious material additive for concrete is prepared from the following raw materials in parts by weight: 80 parts of composite slag powder, 100 parts of composite gelling agent, 10 parts of polyethylene glycol, 6 parts of aluminum sulfate, 6 parts of calcium silicate whiskers, 12 parts of polyacrylonitrile, and 12 parts of Wenlun glue; the composite slag powder is a mixed slag of copper tailings powder and nickel tailings powder mixed in a mass ratio of 3:1; the composite gelling agent is a mixture of ferrous sulfate and polyvinyl acetate mixed in a mass ratio of 3:1.
[0023] The preparation method of the low-carbon cementitious material additive for concrete comprises the following steps: taking 80 parts of composite slag powder, 100 parts of composite gelling agent, 10 parts of polyethylene glycol, 6 parts of aluminum sulfate, 6 parts of calcium silicate whisker, 12 parts of polyacrylonitrile and 12 parts of Wenlun glue according to weight parts, putting them into a mixer and stirring them at 600 rpm for 30 minutes to prepare the low-carbon cementitious material additive for concrete.
[0024] Example 3
[0025] A low-carbon cementitious material additive for concrete is prepared from the following raw materials in parts by weight: 120 parts of composite slag powder, 250 parts of composite gelling agent, 30 parts of polyethylene glycol methacrylate, 18 parts of sodium metasilicate, 10 parts of vanadium slag, 10 parts of basalt fiber, 30 parts of epoxy resin, and 30 parts of montmorillonite; the composite slag powder is a mixed slag of copper tailings powder and nickel tailings powder mixed in a mass ratio of 3:1; the composite gelling agent is a mixture of ferrous sulfate and polyvinyl acetate mixed in a mass ratio of 3:1.
[0026] The low-carbon cementitious material additive for concrete is prepared by taking, according to weight parts, 120 parts of composite slag powder, 250 parts of composite gelling agent, 30 parts of polyethylene glycol methacrylate, 18 parts of sodium metasilicate, 10 parts of vanadium slag, 10 parts of basalt fiber, 30 parts of epoxy resin and 30 parts of montmorillonite, putting them into a mixer and stirring them at 1200 rpm for 60 minutes.
[0027] Comparative Example 1
[0028] A low-carbon cementitious material additive for concrete is prepared from the following raw materials in parts by weight: 100 parts of copper tailings powder, 180 parts of a composite gelling agent, 20 parts of calcium lignin sulfonate, 12 parts of water glass, 12 parts of diatomaceous earth, 20 parts of styrene-butadiene rubber, 10 parts of oleic acid, and 10 parts of triethanolamine; the composite gelling agent is a mixture of ferrous sulfate and polyvinyl acetate in a mass ratio of 3:1.
[0029] The preparation method of the low-carbon cementitious material additive for concrete comprises the following steps: taking 100 parts of copper tailings powder, 180 parts of composite gelling agent, 20 parts of calcium lignin sulfonate, 12 parts of water glass, 12 parts of diatomaceous earth, 20 parts of styrene-butadiene rubber, 10 parts of oleic acid and 10 parts of triethanolamine according to weight parts, putting them into a mixer and stirring them at 800 rpm for 40 minutes to prepare the low-carbon cementitious material additive for concrete.
[0030] Comparative Example 2
[0031] A low-carbon cementitious material additive for concrete is prepared from the following raw materials in parts by weight: 100 parts of nickel tailings powder, 180 parts of a composite gelling agent, 20 parts of calcium lignin sulfonate, 12 parts of water glass, 12 parts of diatomaceous earth, 20 parts of styrene-butadiene rubber, 10 parts of oleic acid, and 10 parts of triethanolamine; the composite gelling agent is a mixture of ferrous sulfate and polyvinyl acetate in a mass ratio of 3:1.
[0032] The preparation method of the low-carbon cementitious material additive for concrete comprises the following steps: taking 100 parts of nickel tailings powder, 180 parts of composite gelling agent, 20 parts of calcium lignin sulfonate, 12 parts of water glass, 12 parts of diatomaceous earth, 20 parts of styrene-butadiene rubber, 10 parts of oleic acid and 10 parts of triethanolamine according to weight proportions, putting the mixture into a mixer and stirring the mixture at 800 rpm for 40 minutes to prepare the low-carbon cementitious material additive for concrete.
[0033] Comparative Example 3
[0034] A low-carbon cementitious material additive for concrete is prepared from the following raw materials in parts by weight: 100 parts of composite slag powder, 180 parts of ferrous sulfate, 20 parts of calcium lignin sulfonate, 12 parts of water glass, 12 parts of diatomaceous earth, 20 parts of styrene-butadiene rubber, 10 parts of oleic acid, and 10 parts of triethanolamine; the composite slag powder is a mixed slag obtained by mixing copper tailings powder and nickel tailings powder in a mass ratio of 3:1.
[0035] The preparation method of the low-carbon cementitious material additive for concrete comprises the following steps: taking 100 parts of composite slag powder, 180 parts of ferrous sulfate, 20 parts of calcium lignin sulfonate, 12 parts of water glass, 12 parts of diatomaceous earth, 20 parts of styrene-butadiene rubber, 10 parts of oleic acid and 10 parts of triethanolamine according to weight parts, putting them into a mixer and stirring them at 800 rpm for 40 minutes to prepare the low-carbon cementitious material additive for concrete.
[0036] Comparative Example 4
[0037] A low-carbon cementitious material additive for concrete is prepared from the following raw materials in parts by weight: 100 parts of composite slag powder, 180 parts of polyvinyl acetate, 20 parts of calcium lignin sulfonate, 12 parts of water glass, 12 parts of diatomaceous earth, 20 parts of styrene-butadiene rubber, 10 parts of oleic acid, and 10 parts of triethanolamine; the composite slag powder is a mixed slag obtained by mixing copper tailings powder and nickel tailings powder in a mass ratio of 3:1.
[0038] The preparation method of the low-carbon cementitious material additive for concrete comprises the following steps: taking 100 parts of composite slag powder, 180 parts of polyvinyl acetate, 20 parts of calcium lignin sulfonate, 12 parts of water glass, 12 parts of diatomaceous earth, 20 parts of styrene-butadiene rubber, 10 parts of oleic acid and 10 parts of triethanolamine according to weight parts, putting them into a mixer and stirring them at 800 rpm for 40 minutes to prepare the low-carbon cementitious material additive for concrete.
[0039] Experimental example:
[0040] The gel material cement adopts ordinary silicate cement (PO 42.5R), the aggregate material adopts natural sand (river sand), the additive adopts the additive prepared in Example 1, and the concrete is prepared. The additive content in the concrete dry material is 8%, the cement content is 10%, 15%, 20%, 25%, 30%, 35%, and 40%, respectively, and the balance is natural sand. The mass ratio of dry material to water is 1:0.44; concrete specimens (curing 28d) are prepared according to the conventional method.
[0041] The compressive strength of concrete was tested in accordance with the relevant provisions of the National Standard of the People's Republic of China "Standard for Test Methods of Mechanical Properties of Ordinary Concrete" (GB / T 50081-2002). The specimen size was 100mm×100mm×100mm, 3 in each group, and the reduction factor was 0.95. The test results are shown in Table 1:
[0042] Table 1
[0043]
[0044] It can be seen from Table 1 that when the cement addition amount is less than 10%, the compressive strength of the prepared concrete is too low to be used. When the addition amount is higher than 30%, the increase in compressive strength is not obvious. The optimal cement content that can maintain the compressive strength of concrete and reduce the amount of cement used is 25%.
[0045] The additives prepared in Examples 1-3 and Comparative Examples 1-2 were used as admixtures, with an addition amount of 8%, a cement addition amount of 25%, and a natural sand addition amount of 67%; the mass ratio of dry material to water was 1:0.44; concrete specimens were prepared according to conventional methods (curing for 28 days), and the compressive strength of the prepared concrete was measured. The test results are shown in Table 2:
[0046] Table 2
[0047]
[0048] Note: * represents P < 0.05 compared with Example 1.
[0049] The additives prepared in Examples 1-3 and Comparative Examples 3-4 were used as admixtures, with an addition amount of 8%, a cement addition amount of 25%, and a natural sand addition amount of 67%; the mass ratio of dry material to water was 1:0.44; after stirring evenly, the concrete slump test was carried out. The experiment was carried out in accordance with the relevant provisions of the National Standard of the People's Republic of China "Standard for Test Methods for Performance of Ordinary Concrete Mixtures" (GB / T50080-2002), with 3 in each group. The test results are shown in Table 3:
[0050] Table 3
[0051]
[0052] Note: * represents P < 0.05 compared with Example 1.
[0053] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A low-carbon cementitious material additive for concrete, characterized in that: The invention is made of the following raw materials in parts by weight: 80-120 parts of composite slag powder, 100-250 parts of composite gelling agent, 10-30 parts of water reducing agent, 6-18 parts of activator, 5-20 parts of reinforcing agent, 10-30 parts of adhesive and 10-30 parts of stabilizer; the composite slag powder is a mixed slag of copper tailings powder and nickel tailings powder mixed in a mass ratio of 3:1; the composite gelling agent is a mixture of ferrous sulfate and polyvinyl acetate mixed in a mass ratio of 3:
1.
2. The low-carbon cementitious material additive for concrete according to claim 1, characterized in that: The water reducer is one or more of polyethylene glycol, calcium lignin sulfonate, aminobenzenesulfonic acid, polyethylene glycol methacrylate, and polycarboxylic acid water reducer.
3. The low-carbon cementitious material additive for concrete according to claim 1, characterized in that: The activator is one or more of water glass, aluminum sulfate and sodium metasilicate.
4. The low-carbon cementitious material additive for concrete according to claim 1, characterized in that: The reinforcing agent is one or more of vanadium slag, diatomaceous earth, white carbon black, calcium silicate whisker and basalt fiber.
5. The low-carbon cementitious material additive for concrete according to claim 1, characterized in that: The adhesive is one or more of epoxy resin, sodium carboxymethyl cellulose, gum arabic, polyacrylonitrile, styrene-butadiene rubber and polyacrylamide.
6. The low-carbon cementitious material additive for concrete according to claim 1, characterized in that: The stabilizer is one or more of oleic acid, triethanolamine, weinberg gum, kaolinite and montmorillonite.
7. The method for preparing the low-carbon cementitious material additive for concrete according to claim 1, characterized in that: According to weight proportions, 80-120 parts of composite slag powder, 100-250 parts of composite gelling agent, 10-30 parts of water reducing agent, 6-18 parts of activator, 5-20 parts of reinforcing agent, 10-30 parts of adhesive and 10-30 parts of stabilizer are put into a blender and stirred at 600-1200 rpm for 30-60 minutes to prepare the product.
8. The use of the low-carbon cementitious material additive for concrete according to claim 1 in preparing concrete with low cement dosage, characterized in that: The amount of cement in the low-cement concrete is 15-30% of the mass of the solid material.
Citation Information
Patent Citations
Dry-mixed mortar prepared from industrial solid waste
CN106007561A
Adhesive for cement foundation curing repairing
CN110028289A